(untitled) (Fiep Bulletin - online, 2017)
This study aimed to compare the levels of physical fitness among students in the city of Caceres, Mato Grosso,comparing performance between students from public and private schools. For this survey was conducted including 87 students,aged 11 and 12 years, male and female, 49 students of Public School and 38 students Private School, using the tests andmeasures battery (GAYA , 2005), weight (body mass), Height (Height), BMI (body mass Index), Build, Abdominal, Horizontal Leap(Force Upper Extremities) Medicinebol (Strength Upper Extremities), Flexibility, Agility, Speed, Member Resistance superiorsGeneral and resistance. Also the questionnaire was used to identify the main living habits, divided into socioeconomiccharacterization, everyday organization, socio-cultural participation and sports practices. It was found that for most tests there waslittle significant difference only in the flexibility test was verified significance between the two schools, a fact explained by the greatdifference in the level of education of parents and the pattern of family life. The results of other tests were balanced, BMI (BodyMass Index) proved to be within the normal range for the vast majority of students. Compared to the Standards Table nationallyreferenced to sportspeople, between Genders, there were positive results for Strength testing of the lower limbs and resistance,and negative for flexibility.